Pelatihan Pembuatan Buket Snack Untuk Meningkatkan Kreativitas Santriwati dalam Membuka Peluang Usaha Kerja di Ponpes Sunan Ampel Rejomulyo - Ahmad, Risna Ahmad Nuraini; Arifin, Muhammad Alwan Riza; Nuraini, Risna Ahmad; Rofiah, Nihayatur; Kusumawardhany, Sayekti Indah (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Rabithaah Ma'ahid Islamiyah on August 9, 2024 held a snack bouquet making training to improve the creativity and skills of female students in opening up business opportunities. This training was held at the Sunan Ampel Rejomulyo Islamic Boarding School, Kediri, with around 50 participants who were representatives of Islamic boarding schools in Kediri Regency and City. This activity is in collaboration with the Calalily & Mucha Griya Seserahan bouquet community. The service method used in the training includes theoretical explanations, introduction to tools and materials, and direct practice in small groups. Participants are taught basic techniques for making snack bouquets, from design to product completion. This training also includes an explanation of the purpose of making bouquets as products of economic value. The results of the activity showed an increase in participants' understanding of bouquet making techniques and creativity in creating products. This training succeeded in motivating female students to develop independent, skills-based businesses.